Pengaruh Pembelajaran Aktivitas Gerak Berirama terhadap Peningkatan Keseimbangan dan Kelincahan Gerak - Tio Ilham Wahyudi; Ricky Wibowo; Mukhlisin Mukhlisin (Universitas Hamzanwadi, 2026)
Balance and agility are fundamental motor components that support movement proficiency and physical performance among elementary school students. This study aimed to examine the effect of rhythmic movement learning on improving students’ dynamic balance and agility. The research employed a quantitative approach using a pre-experimental method with a One-Group Pretest-Posttest design. The sample consisted of 32 fourth-grade students from SDN 205 Neglasari, Bandung City, selected through a total sampling technique. Data were collected using the Modified Bass Test of Dynamic Balance to assess dynamic balance and the TKSI Phase B T-Test to measure agility. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and a paired sample t-test, and Cohen's d effect size analysis. The results showed a significant improvement in dynamic balance (t(31) = -38.906; p < 0.001; N-Gain = 0.437; d = 2,495) and agility (t(31) = 9.291; p < 0.001; N-Gain = 0.314; d = 0.680). These findings indicate that rhythmic movement learning can be an effective and engaging physical education approach for enhancing motor skill development among elementary school students.